Ratchet up or down? An experimental investigation of global public good provision in the United Nations Youth Associations Network - Carlo Gallier; Martin Kesternich; Andreas Löschel; Israel Waichman (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2018)
From a current perspective the Paris Agreement is not sufficient to limit the global mean temperature below 2êC above pre-industrial level as intended. The Agreement stipulates that parties review, compare and ratchet up efforts to combat climate change over time. Within this process, commitments heavily depend on what has been already achieved and this status-quo reflects an important reference point serving either as commitment advice or potential threat. We present an experimental study that is specifically designed to incorporate the effect of a status-quo via pre-existing contribution levels under endowment heterogeneity in a game in which participants make voluntary contributions to a public good. Our participants are sampled from the United Nations Youth Associations Network, representing participants from 51 countries. Members from developed and developing countries take decisions against the background of different initial levels of endowments and pre-existing contributions. Our analysis indicates that starting with ambitious pre-existing contribution levels can foster aggregate mitigation levels. Falling behind this status-quo contribution levels by reducing the public good appears to be a strong behavioral barrier. These observations might provide support for the basic structure of the Paris Agreement with Nationally Determined Contributions and the possibility to adjust them, even if a downward revision of national targets may not be precluded.
Keywords: H41; C91; F53; Q58; 330; Paris Agreement; Nationally Determined Contributions; Ratched-up mechanism; International public goods; Online experiment